2017
DOI: 10.1007/s00066-016-1091-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in desmoid tumors

Abstract: Radiotherapy is a valuable option for treating desmoid tumors. Radiotherapy dose appears to be significantly associated to local control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Radiotherapy may be useful for unresectable or recurrent DF as well as in patients who are at high risk for surgery [6164]. Further, adjuvant radiotherapy following surgery may also be considered in DF, especially those with positive surgical margins [64].…”
Section: Managementmentioning
confidence: 99%
“…Radiotherapy may be useful for unresectable or recurrent DF as well as in patients who are at high risk for surgery [6164]. Further, adjuvant radiotherapy following surgery may also be considered in DF, especially those with positive surgical margins [64].…”
Section: Managementmentioning
confidence: 99%
“…In fact, the role of postoperative adjuvant radiotherapy has been controversial in the past few decades. Different studies have come to different conclusions (28)(29)(30)(31). A meta-analysis has indicated that adjuvant radiotherapy can reduce the recurrence rate of patients with positive resection margins, but for patients with negative resection margins, adjuvant radiotherapy cannot reduce recurrence or improve the local control rate (32).…”
Section: Discussionmentioning
confidence: 99%
“…Khorsand and Karakousis 21 reported that radiotherapy reduced the recurrence of MF to 20%–40% compared to 40%–70% reduction achieved with surgery only. Santti et al 22 also concluded that radiotherapy was a valuable option for the treatment of desmoid tumors. In addition, chemotherapy (vincristine, cyclophosphamide, and dactinomycin – either alone or in combination), non-steroidal anti-inflammatory drugs, hormonal manipulation (tamoxifen, aromatase inhibitors, and gonadotropin), and molecular target therapy (imatinib, sorafenib, and sunitinib) may be alternative choices.…”
Section: Discussionmentioning
confidence: 99%